2022
DOI: 10.3389/fonc.2022.927358
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of CCDC102B by Loss of RACK1 Through the CMA Pathway Promotes Breast Cancer Metastasis via Activation of the NF-κB Pathway

Abstract: BackgroundBreast cancer is one of the leading causes of cancer-related death among women, and the pathological status of axillary lymph nodes is an important predictor of prognosis. However, the mechanism involved in this early stage of metastasis remains largely unknown.MethodsMicroarray analysis was used to carry out differential genomics analyses between matched pairs of metastatic sentinel lymph node tissues and breast primary tumors. The CRISPR/Cas9 gene editing system was used for in vivo screening by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Thus, the genes in the signature might be important in breast cancer metastasis. For instance, CCDC102B was reported to be overexpressed in metastatic lesions and it could facilitate breast cancer metastasis in vitro and in vivo [35]. In our signature, it was also upregulated in epithelial cells of metastatic lymph nodes compared to primary cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, the genes in the signature might be important in breast cancer metastasis. For instance, CCDC102B was reported to be overexpressed in metastatic lesions and it could facilitate breast cancer metastasis in vitro and in vivo [35]. In our signature, it was also upregulated in epithelial cells of metastatic lymph nodes compared to primary cancer.…”
Section: Discussionmentioning
confidence: 66%
“…For example, ENPEP has been shown to be a key factor involved in breast cancer cell proliferation through the function of inducing G2/M cell cycle arrest and reducing anchorageindependent cell growth of mammary origin (36). Si and colleagues claimed that coiled-coil domain containing 102B (CCDC102B) was apparently increased in metastatic lesions in lymph nodes of breast cancer patients (37). Increased expression of CCDC102B was required for breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous study also showed CMA correlated with cancer metastasis. CMA will promote cancer metastasis through regulates the stabilization of tumorigenesis‐related proteins such as coiled‐coil domain containing 102B (CCDC102B) and receptor for activated C kinase 1 (RACK1) (Si et al, 2022; Thorburn & Debnath, 2011). Following, these evidence indicated that CMA which as a mechanism to regulated target protein degradation then affect cancer cell biological functions such as migration and invasion.…”
Section: Discussionmentioning
confidence: 99%